Study on the Weakening Law and Classification of Rock Mass Damage under Blasting Conditions - Rui Yue; Kegang Li; Qingci Qin; Mingliang Li; Meng Li (Energies, 2022)
To study the effects of declining mechanical parameters caused by blasting excavation on slopes, we introduced the damage degree index Ds, and established a relationship between Ds and the disturbance factor D in the Hoek–Brown criterion, along with a basic quality index BQ for the rock mass. We then explored the change law for the degree of rock damage Ds as a function of the disturbance factor D. We also used a phosphate mine slope in Guizhou Province for reference, and analyzed the process of damage evolution of the slope based on the RHT (Riedel-Hiermaier-Thoma Constitution) in LS-DYNA (Yunnan, China). Results showed a direct relationship between the GSI value in the Hoek–Brown criterion and the initial damage degree of the slope. As Ds increases, D increases exponentially. However, the compressive strength, elastic modulus, cohesion, and internal friction angle decreased nonlinearly, and the tensile strength of the rock mass decreased linearly. Among these parameters, the compressive strength decreased the most rapidly, while the internal friction angle decreased slowly. We also established a new grade for rock self-stabilization with Ds as the evaluation standard. Thus, these results may provide a theoretical basis for determining the mechanical properties of rocks for future slope protection and stability evaluations.